THE METHODS OF APPRAISAL OF TECHNICAL STATE OF ROTOR EQUIPMENT ACCORDING TO VIBRATION, APPLIED AT RUP «BMZ» FOR DIAGNOSTICS OF THE BASIC AND AUXILIARY EQUIPMENT OF MILLS - A. N. Katsyn (Литьë и металлургия, 2010)
The methods of appraisal of technical state of rotor equipment by vibration, applied at RUP «BMZ» for diagnostics of the basic and auxiliary equipment of the mills are examined.